The use of olive mill wastewater by wild type Yarrowia lipolytica strains : medium supplementation and surfactant presence effect - Lopes, Marlene (2009)
BACKGROUND: The aim of this work was to study the ability of two different wild type strains of the yeast Yarrowia lipolytica to grow on olive mill wastewater (OMW) and their potential to produce high-value products such as lipases. Factors that affect cellular growth and OMW degradation were studied, such as nitrogen supplementation, cells concentration and surfactant addition. RESULTS: Both strains, W29 and IMUFRJ 50682, were able to grow in OMW with 19 g L-1 of COD and approximately 800 mg L-1 of total phenols concentration. The strain W29 presented the highest potential for extracellular lipase production in OMW medium. Lipase productivity was improved by the medium supplementation with ammonium sulphate up to 6 g L-1, leading to 80% of COD degradation and 70% of total phenols reduction. The surfactant Tween 80 enhanced cell growth and COD degradation, but had a negative effect on lipase activity. CONCLUSIONS Y. lipolytica has a great potential for OMW valorisation by its use as culture medium for biomass and enzymes production. The operating conditions that favoured lipase production differ from the conditions that improve COD reduction.